The Students’ Needs in Learning English for Tourism at English Study Program in Sintuwu Maroso University - Sherliane Trisye Poai (Sintuwu Maroso Journal of English Teaching, 2016)
The objective of this study was to identify the students’ needs of English Study Program in learning English for Tourism. The type of this study was qualitative descriptive method. The subjects of the study were fourth semester students in academic year 2015/2016 consisted of 44 students. Data were gathered through questionnaire and analyzed descriptively, then interpreted by the researcher. Thefindings of the study revealed that the students felt necessary to learn EFT for their education and career in the future. The students learned EFT to know the description of tourism language and to know everything related to English. Since the students lacked in speaking and writing, their priority in this course had to be on speaking and writing skills that could be done in various activities, for instance, through discussion method. At the end of learning process, the students responded that homework was very important for them. It is expected that the result of the study can be used as a reference to prepare and develop relevant materials for students’ academic and professional needs, especially English for Tourism learning need.Keywords: English for Tourism, students’ needs.